Assessing the impact of urbanization on air pollution and land surface temperature using remote sensing data in Google Earth Engine: A Case Study of Tehran Province (2018–2022) - Asghari Beirami, Behnam; Shobairi, Seyed Omid Reza; Gulahmadov , Nekruz; Hotam, Parvizi; Farhod, Nasrulloev (Ecological Questions, 2025)
This study examines the environmental impacts of urbanisation trends in Tehran Province, Iran, from 2018 to 2022, utilising Visible Infrared Imaging Radiometer Suite (VIIRS) Day/Night Band (DNB) data as a proxy for human activities. Its effects on air pollution (nitrogen dioxide (NO₂), carbon monoxide (CO), and ozone (O₃) from Sentinel-5P and land surface temperature (LST) from Moderate Resolution Imaging Spectroradiometer (MODIS)) were analysed in Google Earth Engine (GEE). VIIRS DNB showed a sharp upward trend, indicating rapid urbanization. NO₂ pollution increased significantly across the region, while CO and O₃ exhibited weak decreasing and increasing trends, respectively. Daytime and nighttime LST rose by approximately 1°C overall, reflecting the urban heat island (UHI) effect despite fluctuations. Correlation analysis (r) revealed strong links between DNB and NO₂/CO (r=0.59–0.72) (a key contribution underscoring urbanisation’s direct emission drivers), moderate with nighttime LST (r up to 0.38), and weak with O₃, underscoring urbanisation’s role in driving pollution and heat. These findings emphasise the need for intensified emission controls, green infrastructure, and sustainable urban planning in rapidly growing cities like Tehran.